NGF-mediated crosstalk: unraveling the influence of metabolic deregulation on the interplay between neural and pancreatic cancer cells and its impact on patient outcomes - Trentini, Francesca; Agnetti, Virginia; Manini, Martina; Giovannetti, Elisa; Garajová, Ingrid (Frontiers in Pharmacology, 2024)
Neural invasion is one of the most common routes of invasion in pancreatic cancer and it is responsible for the high rate of tumor recurrence after surgery and the pain generation associated with pancreatic cancer. Several molecules implicated in neural invasion are also responsible for pain onset including NGF belonging to the family of neutrophins. NGF released by cancer cells can sensitize sensory nerves which in turn results in severe pain. NGF receptors, TrkA and P75 NTR , are expressed on both PDAC cells and nerves, strongly suggesting their role in neural invasion. The crosstalk between the nervous system and cancer cells has emerged as an important regulator of pancreatic cancer and its microenvironment. Nerve cells influence the pancreatic tumor microenvironment and these interactions are important for cancer metabolism reprogramming and tumor progression. In this review, we summarized the current knowledge on the interaction between nerves and pancreatic cancer cells and its impact on cancer metabolism.